Pembinaan Atlet E-Sport Oleh IeSPA (Indonesian E-Sport Assosiaction) Samarinda - Akhmad Reynaldi; Muhammad Jamal Amin; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This research is intended to find out and analyze the development of ESport athletes carried out by IeSPA Samarinda City, whether the coaching that has been carried out is in accordance with the indicators of organization, facilities and infrastructure, coordination, supervision, and planning as well as to find out the obstacles faced in coaching E-Sport athletes by IeSPA Samarinda City. The results of the study show that the coaching carried out by IeSPA Samarinda City for e-sport athletes in Samarinda has been running with the activities that have been carried out for E-Sport athletes. This is proven by the many matches or tournaments between e-sport athletes held by the IeSPA Kota Samarinda so as to hone the abilities of these e-sport athletes. In addition, the output that can be achieved is to be able to find new seeds for the next level. While the obstacles faced in fostering esport athletes by IeSPA Samarinda City are the lack of funds that can be allocated by IeSPA Samarinda City to KONI, the lack of professional clubs that can accommodate e-sport athletes, and the increasing price of mobile devices as playing infrastructure.